Study of Malondialdehyde Levels in sera, RBCs and Tissues homogenate of Iraqi Women With Breast Tumors - Baghdad Science Journal (مجلة بغداد للعلوم, 2009)
Breast tumors patients generally have more oxidative stress than normal females. This was clear from a highly significant elevation (P